Формування та еволюція поняття музейний фонд держави - Рябчикова, Фаїна Денисівна; Riabchykova, Faina D. (Інститут історії України Національної академії наук України, 2016)
Досліджено формування та еволюцію поняття музейний фонд держави. З’ясовано, що воно виникло після жовтневого перевороту 1917 р. у результаті проведеної націоналізації, державної реєстрації пам’яток та побудови системи державного управління музейною справою. Законодавче закріплення сукупного музейного фонду вперше було здійснене в СРСР у середині 1960-х рр. з прийняттям Положення про Музейний фонд Союзу РСР. Після здобуття незалежності в Україні поняття сукупного музейного фонду збереглося в державно-правовому регулюванні музейної галузі. Законом України «Про музеї та музейну справу» (1995 р.) було введено новий термін на його позначення – Музейний фонд України, а також закріплено його правову дефініцію.

The article analyzes the formation and evolution of the concept of the State Museum Fund. It was found that it arose after the Bolshevik Revolution in1917 as a result of nationalization, the state registration of monuments and foundation of the museum public administration system. In 1918−1919 the development of the concept was carried out simultaneously on several levels: the state level (Moscow Declaration), legislative level (project of Decree on the establishment of a single State Museum Fund) and scientific level (Museological works of F. Schmit). Legislating of the total museum fund was made first time in the USSR in the mid-1960s. That was associated with the adoption of Regulation on the Museum fund of the USSR. Development of museological knowledge and improving of organization of the museum work have led to a clarification of the definition of the Museum Fund of the USSR in the late 1980s. After independence in Ukraine the concept of the State Museum Fund was preserved in state legislation on museum area. Law of Ukraine "On Museums and Museum Affairs" (1995) introduced a new term for concept of the State Museum Fund − Museum Fund of Ukraine and assigned its legal definition.

Исследовано формирование и эволюцию понятия музейный фонд государства. Выяснено, что оно возникло после октябрьского переворота 1917 г. в результате проведенной национализации, государственной регистрации памятников и построения системы государственного управления музейным делом. Законодательное закрепление совокупного музейного фонда впервые было осуществлено в СССР в середине 1960-х гг. с принятием Положения о Музейном фонде Союза ССР. После обретения независимости в Украине понятие совокупного музейного фонда сохранилось в государственно-правовом регулировании музейной отрасли. Законом Украины «О музеях и музейном деле» (1995 г.) был введен новый термин на его обозначение − Музейный фонд Украины, а также закреплено его правовую дефиницию.
Формирование и эволюция понятия музейный фонд государства
Formation and evolution of the concept of the State Museum Fund
Keywords: сукупний музейний фонд держави; Музейний фонд Союзу РСР; Музейний фонд України; на справа; совокупный музейный фонд государства; Музейный фонд Союза ССР; музейное дело; Total Museum Fund of the State; Museum Fund of the USSR; museum studies; Museum Fund of Ukraine; Музейный фонд Украины